All Days 1993
DOI: 10.2118/26925-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2/Sand Fracturing in Devonian Shales

Abstract: A total of five carbon dioxide (CO2) /sand well stimulations were successfully executed with two Devonian shale operators in Perry and Pike Counties, Kentucky. This new stimulation method offers a minimum formation damage proppant stimulation approach for natural gas producers in the United States. Some operators have been concerned about the frac fluid formation damage associated with the water and chemicals used in conventional foam stimulations, whereas other operators have been concerned abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…A 100% increase in gas production over that baseline would consititute a PIF of 2. A limited number of industry and Department of Energy-sponsored pilot sites have explored the efficacy of CO 2 -based fracs to date across the U.S. and Canada, such as the Lewis Shale (NM), Devonian shale (KY), , Canyon Sands (TX), and scattered early vertical frac wells . For the base case, results compiled from a comprehensive literature review of actual CO 2 frac jobs were applied to project CO 2 performance.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 100% increase in gas production over that baseline would consititute a PIF of 2. A limited number of industry and Department of Energy-sponsored pilot sites have explored the efficacy of CO 2 -based fracs to date across the U.S. and Canada, such as the Lewis Shale (NM), Devonian shale (KY), , Canyon Sands (TX), and scattered early vertical frac wells . For the base case, results compiled from a comprehensive literature review of actual CO 2 frac jobs were applied to project CO 2 performance.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…In spite of the qualitative arguments for using CO 2 as a working fluid, few studies provide quantitative comparisons of the technical performance or the systems-level (e.g., logistics and life cycle) implications of using CO 2 instead of water for fracturing shale formations. Several studies have documented the efficacy of liquid-free CO 2 /sand stimulations in the U.S. and Canada, but these did not provide clear comparisons between working fluids in the same formations. Heath et al summarize GHG life cycle assessments (LCA) for water-based fracs from multiple shale gas studies .…”
Section: Introductionmentioning
confidence: 99%
“…Initial trials focused on using CO 2 as a miscible fluid to displace oil from reservoirs, with CO 2 being injected as a liquid from the wellhead. In order to enhance the performance of CO 2 fracturing and flooding, CO 2 was combined with foam-based fracturing techniques, leading to the development of CO 2 foam fracturing in the early 2000s (Martin and Taber, 1992;Yost et al, 1993). The use of foam in CO 2 fracturing offers several advantages over traditional hydraulic fracturing methods.…”
Section: History and Restricted Definition Of Co Fracturingmentioning
confidence: 99%
“…Companies and researchers have been working hard to identify nonaqueous working fluids that offer an opportunity to enhance production, reduce water usage, and lessen environmental effects. Moreover, studies have shown that Sc-CO 2 is a more efficient nonaqueous working fluid than water in extracting gas from shale gas reservoirs. This can be explained by the unique physical and chemical properties of Sc-CO 2 . In comparison to water-based fracturing fluids, Sc-CO 2 avoids huge flowback wastewater disposal and formation damage because of its water sensitivity, resulting in environmentally friendly performance. , Supercritical carbon dioxide (CO 2 ) exhibits properties that lie between those of a gas and a liquid, when it is under pressures and temperatures greater than 7.38 MPa and 31.1 °C, respectively. ,, In laboratory experiments, researchers found that CO 2 in its supercritical state has strong rock-breaking capacity and can infiltrate any space larger than its kinetic diameter (0.330 nm) due to its strong permeability, low viscosity, and extremely low surface tension like gas. It can fracture rock at lower fracturing pressure and form multiple highly complex fracture networks, which enhance oil and gas recovery by displacing remaining hydrocarbon and create a great potential for CO 2 geo-storage. ,,,,, …”
Section: Introductionmentioning
confidence: 99%